Research on determining the aseismic performance level of reinforced concrete building - Jong-Bom Han (International Journal of Architecture and Urbanism, 2021)
In seismic design based on performance, seismic performance level is determined based on failure state of the building and seismic design objective is set according to the importance of the buildings. In many countries, they calculate the seismic reaction of the buildings with the use of structural design programs to check the aseismic performance through the nonlinear static analysis method. In this paper, we established seismic performance levels and aseismic design objective to design on the basis of design objective according to the three levels in Seismic Design Code of Building, DPR Korea, 2010.